Analisis Tingkat Kepuasan Kerja Karyawan pada PT Hatten Bali di Denpasar - BILL CLINTON TUAN PARMONANG; DWI PUTRA DARMAWAN; PUTU UDAYANI WIJAYANTI (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2018)
The Analysis of Employee’s Job Satisfaction Rate in the PT Hatten Bali in Denpasar This research is aimed to acknowledge the employee’s work satisfaction rate in PT Hatten Bali to build a good result in this company. The method which used to collect the data was survey, observation, and interview. The total respondents were 113 employees who were streamlined by using Slovin Formula and reach 53 samples for eficiency. The samples were taken by purposive sampling. The analyzed data was qualitative descriptive.The result of the research according to the economy factor and social factor shows that the percentage rate of employee’s work satisfaction is satisfied. The percentage of economic factor and social factor based on questioner are 68,11% and 75,20%. The highest percentage according to the questioner is satisfaction to work environment by 82,19%. The achievement of the lowest percentage based on questioner is satisfaction to award distribution which reach 66,11% and will be followed by economic factor in satisfaction to salary and reward received by the employees reach 68,11%, satisfaction to the attitude of their superior reach 72,75%, satisfaction to their co-workers reach 76,60% and satisfaction to job itself reach 78,36%.